SUBSTANTIATION OF A RATIONAL METHOD FOR DRYING WHEAT GLUTEN GRANULES IN A FLUIDIZED BED AND INSTALLATION FOR ITS IMPLEMENTATION - A. A. Pokoptseva; I. Yu. Aleksanyan; A. H.-H. Nugmanov; F. E. Vomenko; Yu. A. Maksimenko (Современная наука и инновации, 2023)
The object of research in the article is pre-frozen granules of gluten, which is produced from wheat grain and is used in the form of a powder in the food industry as an improver for the baking parameters of flour. Based on a comparative analysis of methods for dehydrating frozen wheat gluten granules with a dry surface crust, a rational method for drying them in a fluidized bed was chosen. In the variant of the active hydrodynamic mode in the drying unit, the dehydration procedure is intensified without a noticeable decrease in the economic efficiency of its operation and high quality indicators of the finished product with a given final moisture content are provided, which is due to the specific conditions of contact between the granules and the heat carrier. Based on the study of the advantages and disadvantages of known plants for drying gluten granular products, a rational design of the plant for drying gluten granules is recommended. The article provides justifications for the use of the original continuous dryer, which, due to its design features, can be suitable not only for dehydrating the investigated granular semi-finished product, but also for drying similar products.